1992
DOI: 10.1063/1.352247
|View full text |Cite
|
Sign up to set email alerts
|

dc voltage holding experiments of vacuum gap for high-energy ion sources

Abstract: dc voltage holding characteristics were investigated to obtain a data base for designing high-energy and high-power ion sources of neutral beam injectors. We confirmed that the voltage holding characteristics almost obey the clump theory in the experimental gap length of up to 50 mm. The magnetic field in the gap lowered the breakdown voltage in a gas discharge region higher than a pressure of 10−3 Torr. The breakdown voltage of 30% was reduced by seeding cesium on the electrode with one order higher density t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…1, which contains available data that have been taken as reference data for determining the design criteria. The square closed symbols denote BDVs of vacuum gaps between circular oxygen free copper electrodes without field concentration [4]. It is found that the BDV is proportional d 0.5 to 0.6 , where d is the gap length, which is similar to that 0093-3813/$26.00 © 2011 IEEE predicted by "clump theory" [3].…”
Section: A Vacuum Gap Insulation Criteriamentioning
confidence: 81%
See 2 more Smart Citations
“…1, which contains available data that have been taken as reference data for determining the design criteria. The square closed symbols denote BDVs of vacuum gaps between circular oxygen free copper electrodes without field concentration [4]. It is found that the BDV is proportional d 0.5 to 0.6 , where d is the gap length, which is similar to that 0093-3813/$26.00 © 2011 IEEE predicted by "clump theory" [3].…”
Section: A Vacuum Gap Insulation Criteriamentioning
confidence: 81%
“…2 [9]. The data used in the plot are the data measured after BDVs were increased by repetition of conditioning and reached a plateau value after about 20 shots breakdowns [4]. The voltage corresponding to 0.1% breakdown probability in the Weibull plot was defined as withstand voltage 1, as shown as square open symbols in Fig.…”
Section: A Vacuum Gap Insulation Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…The lengths of the ESG-A1G, A1G-A2G, and A2G-GRG gaps are 75mm, 65mm, and 55mm, respectively. The shortest gap length was mainly determined, based upon the R&D results on the voltage holding capability between the grids in vacuum [3]. The other gap lengths were set to converge the D-ion beams by forming electrostatic lenses.…”
Section: Methodsmentioning
confidence: 99%
“…For the geometries typical of the NBI injectors [3] i.e. with gap length above some centimetres -there are experimental evidences of the voltage breakdown tendency to saturate with the gap distance (U proportional to gα, with 0.3<α <0.7), indicating that the breakdown is dominated by the "clump mechanism", proposed first by Cranberg in the fifties [4] or by electron bombardment of the anode when the electron energy exceeds 0.6-0.7 MeV [5].…”
Section: Introductionmentioning
confidence: 99%